How Air Temperature and Solar Radiation Impact Life History Traits in a Wild Insect - Alexandra S. Gardner; Ilya M. D. Maclean; Rolando Rodríguez‐Muñoz; Alfredo F. Ojanguren; Tom Tregenza (Ecology and Evolution)
ABSTRACT Ectotherms are essential components of all ecosystems. They rely on external heat sources like air temperature and solar radiation to regulate their body temperature and optimise life history traits. Climate change, by altering air temperature and cloud cover, will likely impact these processes. To examine how air temperature and shade influence terrestrial insects, we reared nymphs of the field cricket (Gryllus campestris) at high (mean air temperature 13.4°C) and low (mean air temperature 9.6°C) sites in northern Spain, with partially shaded and unshaded treatments at each site. We tested for local adaptation to these climate variables by rearing nymphs from high and low altitude genetic lineages in all treatment combinations. Development time was significantly longer (on average 10 days) at low air temperature but was unaffected by a 40% increase in shade, suggesting crickets compensate for reduced sun exposure in shaded environments and may forgo some opportunities to gain energy from the sun in unshaded environments. Adult mass was affected by an interaction between shade and air temperature. At low air temperature, shaded crickets had higher mass (on average + 0.06 g) than unshaded crickets, whereas at high air temperature, shaded crickets had lower mass than unshaded crickets (on average − 0.08 g). This indicates that changes in cloud cover will impact insects differently in warmer and cooler parts of their range. We found no evidence for local adaptation in either development time or mass, suggesting these traits are not strongly differentiated between populations from high and low altitude environments. Our findings highlight the importance of considering both air temperature and solar radiation when predicting climate change impacts on insects. Shifts in temperature and cloud cover may have complex and region‐specific effects on these vital ecosystem components.